Banking and Currency Crises: Differential Diagnostics for Developed Countries. (7th November 2016) - Joy, Mark; Rusnák, Marek; Šmídková, Kateřina; Vašíček, Bořek
Abstract: We identify a set of 'rules of thumb' that characterize economic, financial and structural conditions preceding the onset of banking and currency crises in 36 advanced economies over 1970–2010. We use the classification and regression tree methodology and its random forest extension, which permits the detection of key variables driving binary crisis outcomes, allows for interactions among key variables and determines critical tipping points. We distinguish between basic country conditions, country structural characteristics and international developments. We find that crises are more varied than they are similar. For banking crises, we find that low net interest rate spreads in the banking sector and a shallow, or inverted, yield curve is their most important forerunners in the short term. In the longer term, it is high house price inflation. For currency crises, high domestic short‐term rates coupled with overvalued exchange rates are the most powerful short‐term predictors. We find that both country structural characteristics and international developments are relevant banking‐crisis predictors. Currency crises, however, seem to be driven more by country idiosyncratic, short‐term developments. We find that some variables, such as the domestic credit gap, provide important unconditional signals, but it is difficult to use them as conditional signals and, more importantly, to find relevant threshold values. Copyright © 2016 John Wiley & Sons, Ltd.